2020
DOI: 10.1038/s41598-020-58370-3
|View full text |Cite
|
Sign up to set email alerts
|

Reversed Doppler effect based on hybridized acoustic Mie resonances

Abstract: The realization of reversed Doppler effects in double-negative acoustic metamaterials remains challenging. This paper demonstrates the reversed Doppler effect associated with sound wave propagation in negative group velocity in hybridized metamaterial (HM) system using a simple Mieresonator configuration. Double-negative acoustic parameters act simultaneously on the effective dynamic bulk modulus and mass density within overlapped frequency region of multiple Mie resonances. Notably, while ordinary media exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…As illustrated in figure 1 b , the design of the SCM unit cell involves two identical ventilation channels located on the top and bottom of the coupling unit and a curled channel connecting the upstream and downstream with a space-coiling path. Space-coiling designs are usually used to generate linear resonances with optimal occupied space [8] and present an excellent capability to control the frequency distribution of not only fundamental but also higher-order modes [36,37]. In this work, these strategies are employed to manipulate the local resonances and the resulting Fano resonances uniformly over the frequency region of interest.…”
Section: Theoretical Formulation Of Fano-based Metamaterialsmentioning
confidence: 99%
“…As illustrated in figure 1 b , the design of the SCM unit cell involves two identical ventilation channels located on the top and bottom of the coupling unit and a curled channel connecting the upstream and downstream with a space-coiling path. Space-coiling designs are usually used to generate linear resonances with optimal occupied space [8] and present an excellent capability to control the frequency distribution of not only fundamental but also higher-order modes [36,37]. In this work, these strategies are employed to manipulate the local resonances and the resulting Fano resonances uniformly over the frequency region of interest.…”
Section: Theoretical Formulation Of Fano-based Metamaterialsmentioning
confidence: 99%
“…Manipulation and design of acoustic and electromagnetic metamaterials are the study of controlling waves by designing delicate structures. Some exotic acoustic properties can be obtained in acoustic metamaterials (AMMs) through ordered modulation of sound waves, such as negative reactance [ 1 , 2 ], acoustic cloak [ 3 ], acoustic focusing [ 4 , 5 ], abnormal Doppler characteristics [ 6 , 7 ], and canceling out the distortion layer such as skull [ 8 12 ]. Some scholars have found that by adjusting the parameters of the AMM, the influence of the skull distortion layer on the acoustic wave can be effectively eliminated [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic metamaterials (AMM) have shown extraordinary capabilities to manipulate acoustic fields [1][2][3][4] through novel properties such as such as anisotropic, spatially varying, zero, and negative indices, mass densities, and elastic moduli. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] These properties have enabled novel phenomena including cloaking, [21] enhanced wave transmission, [22][23][24][25][26] and subwavelength imaging. [27] In particular, a material that simultaneously has a negative mass density and negative elastic moduli, resulting in a negative acoustic index.…”
Section: Introductionmentioning
confidence: 99%